Zinc Oxide Films Deposited on ITO Through Electrophoresis - Nunes, Vanja Fontenele; Maia Júnior, Paulo Herbert França; Lima, Francisco Marcone; Mota, João Pedro Santana; Freire, Francisco Nivaldo Aguiar; Sombra, Antônio Sérgio Bezerra (Fine Chemical Engineering, 2025)
Films are materials deposited in nanoscale and macroscale thicknesses applied in different fields, like energy harvesting, solar cells, batteries, capacitors, or gas sensors. There are many ways to synthesize and deposit films on conductive glass, such as indium tin oxide or fluorine tin oxide. Some methods can use high temperatures, vacuum, additives, or applied potentials. Electrophoresis can deposit films of various thicknesses with high quality. This work deposited zinc oxide films on conductive glass made of indium tin oxide for testing as solar cell photoanodes. The deposition used an electrophoretic cell, with a difference in electrical potential between 30 and 50 V for 5 minutes. The thickness of the films varied between 18 and 87 μm. The band gap increased with more material deposited on the glass, from 3 to 4 eV. The results show high crystalline quality, a size range from 30 to 40 nm, absorbance in the ultraviolet range, and a current density of around 2.5 mA/cm2 when depositing at 30 V for 5 minutes using the electrophoresis methodology. The aim of this study was to develop a cost-effective method to produce semiconductors for applications, such as solar cells.